Profile of Drug Use in Outpatients with Multidrug Resistant Tuberculosis (MDR TB) at RSD dr. Soebandi Jember - Nindri Lusiana Safana; Sholihatil Hidayati; Jenie Palupi (Indonesian Pharmacopeia Journal, 2024)
Background: A drug use profile is a description of a drug that can be identified through its characteristics. Multidrug Resistant Tuberculosis (MDR TB) is a tuberculosis disease caused by Myrobacterium Tuberculosis bacteria against two types of OAT drugs, namely rifampicin and isoniazid. Objective:The aim of this study was to determine the profile of drug use in outpatients with Multidrug Resistant Tuberculosis (MDR TB) at RSD dr. Soebandi Jember for the 2023 period. Method:This research is descriptive research with one variable. The research sample was 70 MDR TB outpatients using a random sampling technique. Results: In the results for gender characteristics, the number of male patients was 46 (62%), female 28 (38%). Ages 17-25 years amounted to 10 (13%), ages 26-45 years 31 (42%), ages > 46 years 33 (45%). Length of treatment in initial stage 18 (24%), advanced stage 56 (76%). Combination of 3 drugs bedaquiline - linezoid - cycloserine 14 (31%), bedaquiline - ethambutol - cycloserine 1 (2%), clofazimine - linezoid - bedaquiline 1 (2%), bedaquiline - levofloxacin - ethambutol 14 (31%), ethambutol - levofloxacin - cycloserine 13 (30%), bedaquiline - cycloserine - linezoid 2 (4%), combination of 4 drugs levofloxacin - bedaquiline - ethambutol - clofazimine 10 (34%), clofazimine - ethambutol - bedaquiline cycloserine 12 (42%), clofazimine - bedaquiline - ethambutol - ethionamide 7 (24%). The drug use profile contained 7 types of drugs, namely lefoxloxacin 36 (14%), bedaqualin 60 (24%), Ethambutol 57 (23%), Clofazimine 31 (12%), cycloserine 42 (17%), Linezolid 17 (7%), Ethionamide 8 (3%). Conclusion:In the results, the highest number of male gender characteristics was 46 people (62%), the highest age characteristic was >46 years, 33 people (45%), the highest length of treatment characteristic was the advanced stage, namely the advanced stage, 56 people (67%) , the characteristics of the combination of drugs that are widely used are a combination of 3 drugs, there are 2 groups, including 14 people (31%) of bedaquiline - lienezoid - cycloserine and 14 people (31%) of bequiline - levofloxacin - ethambutol, the profile of the most widely used drug is bedaquiline 60 people (24%).